TMBIM5 is the Ca2+/H+ antiporter of mammalian mitochondria. (2nd November 2022) - Austin, Shane; Mekis, Ronald; Mohammed, Sami E M; Scalise, Mariafrancesca; Wang, Wen‐An; Galluccio, Michele; Pfeiffer, Christina; Borovec, Tamara; Parapatics, Katja; Vitko, Dijana; Dinhopl, Nora; Demaurex, Nicolas; et al.
Abstract: Mitochondrial Ca 2+ ions are crucial regulators of bioenergetics and cell death pathways. Mitochondrial Ca 2+ content and cytosolic Ca 2+ homeostasis strictly depend on Ca 2+ transporters. In recent decades, the major players responsible for mitochondrial Ca 2+ uptake and release have been identified, except the mitochondrial Ca 2+ /H + exchanger (CHE). Originally identified as the mitochondrial K + /H + exchanger, LETM1 was also considered as a candidate for the mitochondrial CHE. Defining the mitochondrial interactome of LETM1, we identify TMBIM5/MICS1, the only mitochondrial member of the TMBIM family, and validate the physical interaction of TMBIM5 and LETM1. Cell‐based and cell‐free biochemical assays demonstrate the absence or greatly reduced Na + ‐independent mitochondrial Ca 2+ release in TMBIM5 knockout or pH‐sensing site mutants, respectively, and pH‐dependent Ca 2+ transport by recombinant TMBIM5. Taken together, we demonstrate that TMBIM5, but not LETM1, is the long‐sought mitochondrial CHE, involved in setting and regulating the mitochondrial proton gradient. This finding provides the final piece of the puzzle of mitochondrial Ca 2+ transporters and opens the door to exploring its importance in health and disease, and to developing drugs modulating Ca 2+ exchange. Synopsis: TMBIM5 mediates mitochondrial Ca 2+ /H + exchange and interacts with the K + /H + exchanger LETM1 to maintain mitochondrial pH, Ca 2+ and K + homeostasis. The K + /H + exchanger LETM1 was proposed to mediate mitochondrial Ca 2+ /H + exchange. Transmembrane BAX Inhibitor Motif containing protein 5 (TMBIM5) interacts with LETM1 and maintains mitochondrial K + /H + exchange. TMBIM5, but not LETM1, mediates pH‐dependent mitochondrial Ca 2+ extrusion. TMBIM5 regulates cell metabolism by setting the mitochondrial proton gradient. Abstract : TMBIM5 mediates mitochondrial Ca 2+ /H + exchange and interacts with the K + /H + exchanger LETM1 to maintain mitochondrial pH, Ca 2+ and K + homeostasis.